Spitzenkörper assembly mechanisms reveal conserved features of fungal and metazoan polarity scaffolds - Peng Zheng (Nature Portfolio, 2020)
The Spitzenkörper (SPK) is a polarized accumulation of proteins and secretory vesicles associated with tip growth of fungal hyphae. Here, Zheng et al. study SPK assembly and dynamics, identify SPK protein scaffolds and associated proteins, and reveal similarities with other scaffolds from metazoans.